Moral Transformation and Local Identity: Reviving the Culture of Shun at Temples and Monuments across China. (July 2015) - McNeal, Robin
The article explores recent restoration of ancient temples and the creation of new, modern monuments dedicated to the legendary sage ruler Shun, considered one of the "founding fathers" of the Chinese people and state. The article shows how local elites have tried to build a sense of their community's historical and moral identity while at the same time pursuing economic and political advantage through the promotion of cultural sites. Drawing on time-honored symbols and narratives that celebrate the unity of the Chinese state, these local constructions of Chinese identity promote the local and regional while integrating with higher levels of social and political organization, ultimately re-creating and reinforcing the Chinese nation and, through an appeal to Sinophone sentiment, extrapolating a global Chinese identity. The powerful hold that historical memory still has on people's imaginations is revealed through an examination of prominent temple sites in two locales, in southwestern Hunan and northern Zhejiang.